Key words: right to education - artistic education - in prison education - young and adults education. - Cristiane Carmo dos Santos; Josimara Santos Miranda; José Jackson Reis dos Santos (Universidad Nacional del Nordeste, 2022)
The article describes and examines curriculum practices constructed in the context of a state public school in the State of Bahia, Brazil. It emphasizes curricular experiences planned for the specific context of the Covid-19 pandemic with students (inmates) in the period from March 2021 to December 2021, aiming to ensure the right of education in prison. It discusses practices developed in Youth, Adult and Elderly Education with people in situation of deprivation of freedom, socializing challenges, and possible curriculum constructions through remote teaching. The research data indicate that the penitentiary unit shows contradictory sensations. It is located outside the urban perimeter. The access to the institution recalls bucolic landscapes. However, when approaching this context, fences, watchtowers, and all the maximum security apparatus of an incarceration unit are imposed. In this context, there are also dreams, projects, and lives behind bars that cry out for more justice, for more education, and that consider educators as links of hope, essential in the daily life of the penitentiary unit, bridges between the world of freedom and the world of prison.